A study on Effectiveness of educational intervention on knowledge regarding rabies among high school students in Trivandrum, Kerala - Shaliet Rose Sebastian (Indian Journal of Basic and Applied Medical Research, 2018)
Background: Rabies is an infectious viral disease that is almost always fatal following the onset of clinical symptoms. Objective: To assess the knowledge among high school children on rabies, to impart health education about rabies and to study the change in knowledge after the educational intervention.Methods: A cross sectional study was conducted among 200 high school children at Government Higher Secondary School, Venjaramoodu, Trivandrum. Baseline knowledge regarding rabies was assessed using questionnaire method. A health education n regarding rabies was given to these students and knowledge was again tested using same questionnaire after one week. Results: Although all the study participants had heard about rabies, only 70 out of 200 i.e. 35% students knew that dog bite may lead to rabies. The knowledge regarding rabies was found to have a significant change after health education.. Conclusion: Health education in schools is a cost effective approach to prevent animal bite and rabies consequently.